2020
DOI: 10.3390/cells9030747
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Progenitors Derived from Extraocular Muscles Express Higher Levels of Neurotrophins and their Receptors than other Cranial and Limb Muscles

Abstract: Extraocular muscles (EOMs) show resistance to muscle dystrophies and sarcopenia. It has been recently demonstrated that they are endowed with different types of myogenic cells, all of which present an outstanding regenerative potential. Neurotrophins are important modulators of myogenic regeneration and act promoting myoblast proliferation, enhancing myogenic fusion rates and protecting myotubes from inflammatory stimuli. Here, we adapted the pre-plate cell isolation technique to obtain myogenic progenitors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In accordance, the present results show that p75 NTR levels are proportional to fatigue resistance. Indeed, p75 NTR is upregulated in EOM myogenic progenitor cells, in relation to higher proliferative and fusion rates and better regenerative properties ( Carrero-Rojas et al, 2020 ). Thus, p75 NTR seems to be related to selective muscle resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, the present results show that p75 NTR levels are proportional to fatigue resistance. Indeed, p75 NTR is upregulated in EOM myogenic progenitor cells, in relation to higher proliferative and fusion rates and better regenerative properties ( Carrero-Rojas et al, 2020 ). Thus, p75 NTR seems to be related to selective muscle resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophins are important modulators of myogenic regeneration and act by promoting the proliferation of myoblasts, improving myogenic fusion rates and protecting myotubes from stress stimuli, including oxidative stress. As a result, these muscles are better protected against stress and sarcopenia [64].…”
Section: Ngfmentioning
confidence: 99%
“…The transplantation of EOM MuSCs to the limb leads to more vigorous regeneration in the host muscles than in their limb donor counterparts ( Stuelsatz et al, 2015 ). Mechanistic studies indicated that the higher expression of trophic factors in EOM MuSCs, including brain-derived neurotrophic factors and nerve growth factors, may account for the enhanced myogenic activities ( Carrero-Rojas et al, 2020 ).…”
Section: The Architect Of Muscle Regeneration: Satellite Cellsmentioning
confidence: 99%
“…Both the craniofacial muscles and the trunk/limb muscles derive from the mesoderm (Diogo et al, 2015;Cao et al, 2019;Schubert et al, 2019), but there are many embryonic differences. The craniofacial muscles are derivatives of the cranial mesoderm, while the trunk/limb muscles are derivatives of the lateral plate mesoderm, leading to distinct developmental patterns and genetic lineages in the two muscle groups (Vyas et al, 2020).…”
Section: Craniofacial Muscs Are Of Diverse Embryonic Originsmentioning
confidence: 99%